Implementation of Cognitive and Non-Cognitive Based Diagnostic Assessments on Pancasila and Citizenship Education Subjects - Riyon Lahay; Zulaecha Ngiu; Muchtar Ahmad (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Students' learning outcomes are not always related to the teacher's teaching methods, but are influenced by cognitive and non-cognitive variables that play a role in the achievement of student learning outcomes. Therefore, the implementation of diagnostic assessments is needed to identify and overcome these problems. This research aims to see the results of the implementation of cognitive and non-cognitive-based diagnostic assessments in Pancasila and Citizenship Education subjects at SMPN 22 Wekari. The research method used is qualitative with a descriptive approach. Data collection techniques include observation, interviews, and documentation. Primary data sources were obtained from teachers and students, while secondary data were collected through analysis of reports on the implementation of diagnostic assessments, journals, and relevant books. Data analysis techniques were carried out by data reduction, data display, and verification. The results showed that in the cognitive diagnostic assessment, although students' scores in general had reached the standard, there were still a number of students who had not shown maximum understanding of the material. This was influenced by high absenteeism and delays in completing assignments. In the non-cognitive diagnostic assessment, students' learning styles are more dominant in visual style compared to kinesthetic and auditory styles. For learning interests, students were more dominant in the subjects of Maths, Civics, Science, PE, Religion, Social Studies, and Cultural Arts. This study confirms that the non-achievement of learning outcomes is caused by the gap between learning styles and learning interests in Pancasila and Citizenship Education subjects. The recommendation from this study is for education units to conduct interest mapping to maximise student learning outcomes at SMPN 22 Wekari.Keywords: Diagnostic Assessment, Cognitive, Non-Cognitive